The compact circumstellar material of SN 2024ggi: another supernova with a pre-explosion effervescent zone and jet-driven explosion - Noam Soker (The Open Journal of Astrophysics, 2024)
I examine recent theoretical studies and observations of the recent core-collapse supernova (CCSN) SN~20224ggi and find that the likely explanation for its dense, compact circumstellar material is an effervescent model, where parcels or streams of gas are uplifted by stellar convection and pulsation and fall back. The effervescent zone exists alongside the regular wind from the red supergiant (RSG) progenitor of SN~2024ggi. I find that an extended wind-acceleration zone encounters some difficulties in accounting for the required CSM mass. Recent modelling finds the explosion energy of SN~2024ggi to be $E_{\rm exp} > 10^{51}$ erg, and up to $E_{\rm exp} \simeq 2 × 10^{51}$ erg. I examine this explosion energy against a recent study of the delayed neutrino explosion mechanism and find that this mechanism might have some difficulties in accounting for the required energy. This might suggest that the explosion was caused by the jittering jets explosion mechanism (JJEM). This adds to other recent pieces of evidence supporting the JJEM, particularly point-symmetric CCSN remnants.